Maysel's formula in the generalized linear micropolar thermoviscoelasticity (Archives of Mechanics - Test, 2004)
Generalizations of Maysel's formula to generalized linear micropolar thermoviscoelasticity is given. Fundamental solutions in the Laplace transform domain are obtained. The results are applicable to the following generalized thermoelasticity theories: Lord-Shulman theory with one relaxation time, Green-Lindsay theory with two relaxation times, Green-Naghdi theory of type III, and the Chandrasekharaiah and Tzou theory with dual-phase lag, as well as to the dynamic coupled theory. The cases of generalized linear micropolar thermoviscoelasticity of the Kelvin-Voigt model, and the generalized linear micropolar thermoelasticity can be obtained from the given results.